Sharp injuries to blood-borne pathogens among healthcare workers and influencing factors in a tertiary specialist hospital (2019–2022): a retrospective study - Yuanyi Ji; Xiaoling Liu; Guishuang Song; Qiaolan Liu; Ruixin He; Yongzhong Cheng (Scientific Reports)
Abstract To assess the prevalence of sharp injuries among healthcare workers (HCWs) in a tertiary specialist hospital and analyze the influencing factors to improve protective measures and mitigate exposure risks. A retrospective study was conducted using occupational exposure data from 2019 to 2022. Descriptive statistics, univariate analysis, and multivariate logistic regression were used for statistical analysis, focusing on factors such as gender, years of service, occupation, and exposure department. Among 151 reported occupational exposures, 76.16% (115/151) were sharp injuries. Significant differences were observed in age (P < 0.05), years of service (P = 0.04), and year of exposure (P = 0.02). Multivariate analysis revealed that healthcare workers with 1–5 years of service had a lower risk of sharp injuries compared to those with ≤ 1 year of service or > 5 years of service (OR 0.26, 95% CI 0.09–0.76). The risk of sharp injuries was significantly higher in 2021 (during the COVID-19 pandemic) compared to 2019 (OR 4.32, 95% CI 1.23–18.25). Most injuries occurred on the hands, with HBV being the primary blood-borne pathogen. No infections were reported during follow-up. This study highlights the need for tailored interventions and comprehensive protective measures for HCWs with varying years of service, particularly during public health emergencies like COVID-19, to mitigate sharp injuries and enhance occupational safety.